Impacto do exercício físico agudo no perfil metabólico pós prandial em adultos fisicamente aptos - Belli, Taisa [UNESP] (2009)
The ability to rapidly remove triglycerides from plasma may contribute to reduce the rate of coronary disease. Physical activity is positively associated with a decrease in postprandial triglyceride levels, thus contributing effectively to the prevention and reduction of vascular disorders. The objective of this study was to analyze the course of postprandial triglycerides, as well as postprandial blood glucose, total cholesterol, total protein and hematocrit, after acute exercise in physically fit adults. Ten physically fit university students of both genders, with a mean age of 23.2 ± 1.9 years, were submitted to the collection of postprandial blood samples in two situations: control and exercise. In the control group, subjects remained at rest in the morning before the collection of postprandial blood. In the exercise group, the subjects performed a 20-meter shuttle run test, with gradual increases in intensity until exhaustion, in the morning before the collection of postprandial blood. A significant decrease of postprandial triglycerides was observed in the exercise group (p<0.05), whereas blood glucose, total cholesterol, total protein and hematocrit remained unchanged in this condition. We conclude that in physically fit adults acute physical exercise with a gradual increase in intensity until exhaustion was able to reduce postprandial triglyceride levels and may contribute to the prevention of atherosclerosis and the consequent development of associated cardiovascular diseases.